1969
DOI: 10.12669/pjms.305.4351
|View full text |Cite
|
Sign up to set email alerts
|

‘E-learning’ modalities in the current era of Medical Education in Pakistan

Abstract: There are a number of e-Learning modalities, some or all of which may be used throughout a medical, dental, nursing or any other health related undergraduate curriculum. The purpose of this paper is to briefly describe what e-learning is along with some of the modalities, their common advantages and limitations. This publication ends with practical implications of these modalities for Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
13
0
9
Order By: Relevance
“…Asynchronous E-learning involves educational activities without direct and immediate interaction. A webinar is a seminar (presentation, lecture, or workshop) that is conducted over the internet [9]. The results of our study demonstrated that most of our students were not familiar with these two concepts-asynchronous E-learning and webinars.…”
Section: Discussionmentioning
confidence: 75%
“…Asynchronous E-learning involves educational activities without direct and immediate interaction. A webinar is a seminar (presentation, lecture, or workshop) that is conducted over the internet [9]. The results of our study demonstrated that most of our students were not familiar with these two concepts-asynchronous E-learning and webinars.…”
Section: Discussionmentioning
confidence: 75%
“…A study described that video conferencing is considered a remarkable synchronous approach for medical and nursing students of Sub Saharan Africa. 14 Blended learning approach via a Learning Management System (LMS) is also being implemented in few nursing, medical and dental universities in Pakistan [15][16][17] for instance in DOW University of Health Sciences 15,18 and the Aga Khan University. 19 Synchronous and asynchronous video/audio, Virtual Learning Environment (VLE), videoconferences, online discussion forums, Virtual Classroom, Repository and Hypertext are some of the common digital modalities used in Pakistan's medical universities.…”
Section: Discussionmentioning
confidence: 99%
“…One study from Pakistan suggested that webinars or online lectures are the simplest and user friendly modalities to initiate routine academic activities such as those sessions which do not require a practical training such as small classroom discussions or large classroom lectures. 17 While, to ensure the faculty and student have adequate internet connectivity, accessories of digital gadgets at home, maintaining quality of e-learning are the most crucial and serious concerns for all the universities in Pakistan; if these concerns are not addressed, they may lead to cancellation of the semester by the universities. 30 At the same time, professional training and strengthening the confidence in faculty, students and IT professionals at the institutional level must be a major challenge in implementation of e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…There will also be a need to train faculty and students on how to use the system in order to use it efficiently and effectively. 12 Most of the students wanted the lectures to be videotaped. This is very convenient for the teacher as well as the student.…”
Section: Discussionmentioning
confidence: 99%